PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Geovani Sitepu; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2022)
The purpose of this study was to determine the effect of profitability and leverage on tax avoidance by coal mining companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study uses descriptive and associative methods, the sample used is 14 companies that have passed the criteria of 60 samples using purposive sampling method so that the number of samples studied is 42 data. The analysis technique used in this research is descriptive descriptive statistics, classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination test. The results showed that partially there was no significant effect of profitability on tax avoidance, on the contrary, leverage had a significant effect on tax avoidance. Simultaneously, profitability and leverage have a significant effect on tax avoidance in coal sub-sector mining companies listed on the Indonesia Stock Exchange.